REPRESENTASI KESEHATAN MENTAL TOKOH UTAMA TARI DALAM FILM BOLEHKAH SEKALI SAJA KUMENANGIS: ANALISIS SEMIOTIKA ROLAND BARTHES - Hasna Muna Mufidah; Herning Suryo S (Solidaritas, 2025)
Domestic violence is still a serious social issue in Indonesia, with impacts that are not only physical, but also emotional and psychological, especially for women and children. The impact of domestic violence can affect the victim's mental health, such as trauma, anxiety, and depression, which can last in the long term. Film as a mass communication medium has great potential to educate the public about social issues, including mental health due to domestic violence. The film Bolehkah Sekali Saja Kumenangis raises the issue of mental health in the context of family. This research uses Roland Barthes semiotic approach to uncover the representation of mental health in the film Bolehkah Sekali Saja Kumenangis. The method in this study uses a descriptive qualitative method. Data collection in this study used scene documentation, which obtained 12 scenes to be analyzed using Roland Barthes semiotics model. In addition, this research also applies Stuart Hall's theory of representation. Through an analysis that has been carried out, this study yields results that can be concluded that the film Bolehkah Sekali Saja Kumenangis depicts the representation of mental health which is classified as mental health problems, mental illnesses, and positive mental health. Keywords: domestic violence, mental health, semiotics Roland Barthes, film "Bolehkah Sekali Saja Kumenangis"